Urinary Incontinence due to Overactive Detrusor Muscle: A Rare Side Effect of Venlafaxine - Vithyalakshmi Selvaraj; Palanikumar Gunasekar; Suneel Kumar; Imad Alsakaf (Case Reports in Urology)
We report a case of reemergence of urinary incontinence (UI) in a patient with benign prostatic hyperplasia (BPH) after starting treatment with venlafaxine who was stabilized on tamsulosin and finasteride for about 6 years. A 66-year-old Caucasian male with prior history of major depressive disorder developed UI within a week of starting venlafaxine 75 mg per day. He described symptoms in the form of involuntary leakage of urine both during the day and at night. His symptoms of UI resolved after stopping the venlafaxine. To the best of our knowledge, there are only four case reports of venlafaxine induced urinary incontinence which have been published.